Empowering Virtual Calligraphy Expo as a Solution during a Pandemic - Dian Cita Sari; Makmur Harun; Mohd Kasturi Nor Bin Abd Aziz (Journal of Calligraphy, 2022)
This study aims to study how calligraphers respond to the pandemic. This issue is considered important, because all activities involving large numbers of people are postponed. Exhibitions have a broad role for artists and calligraphers. In order to be widely used, the treasures of exhibition innovations need to be made public. Publication of exhibition innovations is one of the efforts to reach a wider community. One of the outreach efforts that can be done during the current pandemic is a calligraphy virtual exhibition. Some things that need to be analyzed are the process of calligraphy virtual exhibition activities; content coverage; and the factors that influence visits to the Exhibition's official website. Through a case study approach, this study attempts to describe some of the things analyzed. The results of the research show that the calligraphy virtual exhibition process can be carried out systematically and sustainably and is even more acceptable in accordance with the will of the times; content coverage is quite diverse; and the factors that influence visits to the Archive's official website can be identified.